Pengaruh Phase Change Material Jenis Dry Ice Gel Terhadap Variasi Temperatur pada Dinding Freezer - Sena, Boni; Suhendra, Bobie; Amanah, Nadia; Setiawan, Reza; Baihaqi Alfakihuddin, Muhammad Lukman (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2024)
The increasing population growth in cities will cause environmental detriments such as global warming and ozone depletion. The electricity need will increase in the future due to the higher temperature in the cities, leading to the higher usage of cooling equipment such as freezers. The current study proposed a method to improve the freezer's energy efficiency by using phase change material of dry ice gel. Most of previous studies only focused on the impact of position of phase change materials on the temperature of wall freezer while no previous studies consider the detailed methodology of measurement and the impact of phase change material based on dry ice gel to the variance of wall temperature. The sensor thermocouple type T and data logger ADAM 6018+ were used to measure the wall temperature of the freezer. The results showed that the sensor thermocouple was verified to the calibrated thermometer with R2 = 0.99. The installation of phase change material based on dry ice gel on the wall freezer could maintain the temperature around 1-2oC while the freezer was turned off for 4, 6, and 8 hours. The efficiency of freezer could be increased from 10% to 30% due to using dry ice gel phase change material. The future study should investigate the various types of phase change materials and the new combination of phase change materials.